Evaluasi Penggunaan Concrete Filled Steel Tubular pada Bangunan Gedung Tahan Gempa - Wahiddin, Wahiddin; Ratnaningsih, Dwi; Zettyara, Devi (Journal of Civil Engineering, 2025)
Concrete Filled Steel Tubular column is a composite element consisting of concrete with or without reinforcement then wrapped with square or round hollow steel. The hollow steel elements in Concrete Filled Steel Tubular (CFST) columns also function as permanent formwork. Thus the Concrete Filled Steel Tubular (CFST) column element can reduce the use of formwork in the construction of earthquake-resistant high-rise buildings. This study aims to determine the effect of using CFST columns on the structure of a 6-story building. The beam and slab elements of the structure are reinforced concrete elements with a concrete compressive strength of 30 Mpa. The research variable is the thickness of hollow steel wrapped concrete columns with or without rebar. The building structure is located in an area with high earthquake intensity. The results showed that the maximum lateral deflection of the structure decreased as the thickness of the steel element increased with a decrease of 14.67% in CFST without rebar and 14.75% in CFST with rebar. The thicker the column wrapping steel element, the smaller the story drift that occurs with a percentage decrease of 14.51% in CFST without rebar and 14.60% in CFST with rebar. Similarly, the design ratio of the CFST Column structure increased in CFST without rebar by 42.67% while CFST with rebar amounted to 42.68%. This shows that the thicker the steel element, the stiffer and stronger the building structure.